Recepcja wczesnochrześcijańskich motywów eucharystycznych w pieśni "Dziękujemy Ci, Ojcze nasz" - Garnczarski, Stanisław (Vox Patrum, 2023)
The song entitled Dziękujemy Ci Ojcze nasz (We thank Thee, our Father) has its textual origin in an ancient document from the first centuries, entitled Didache tu Kyriu dia ton dodeka apostolon tois ethnesin. The document has the character of church instructions, raising various topics and presenting them in the form of commands and guidelines in moral, legal, ascetic and liturgical matters. In our research, we focused our attention on three points in the Didache (9-10 and 14), which describe the celebration of the Eucharist. It’s about thanksgiving to God for the Eucharist, life, faith and eternal life, and a request for the community of the Church and God’s help on the way to unity with God for eternity. The text and melody of the analyzed song were written by Fr. Kazimierz Pasionek in the 1960s. The exact date is unknown. Certainly, it happened before 1968, because that year during the solemn Holy Mass on the occasion of the 25th anniversary of the priesthood of Bishop Jerzy Ablewicz, the combined choirs - clerical and cathedral – performed under the direction of the composer himself after Holy Communion Eucharistic Prayer according to the text of the Didache. Just as the ancient document Didache is a testimony to Eucharistic piety in the first centuries of Christianity, the song Dziękujemy Ci Ojcze nasz is a testimony to Eucharistic piety in the Church in Poland today.